Analysis Of Communication in The Food Divisi of PT. VADCO PROSPER MEGA - Hidayat, Gustina; Kurniasih, Nining; Munggaran, Rani; Nurodin, Nurodin (Journal of Bussines Management Basic, 2024)
The focus of this research is work communication at the Food Division of PT. Vadco Prosper Mega especially the production department, this study aims to find out how the work communication process and how to solve work communication problems between the production department team leader and employees in the Food Division of PT. Vadco Prosper Mega. The method used in this study is a qualitative research method that is natural. The data collection technique is purposive sampling technique, namely taking samples with certain considerations with the number of informants as many as 7 people. Based on the results of the study, it was concluded that the work communication process at the Food Division of PT. Vadco Prosper Mega especially the production department has been running well, especially in terms of fun, influence on attitude, and good relations between superiors and employees and employees with other employees. In terms of understanding and action, this is not fully optimal because there are still some employees who do not understand their work duties and responsibilities and there are still some employees who do not carry out their work duties and responsibilities properly, thus hindering other work.